Effects of Artificial Intelligence on the Academic Performance of Grade 8 Students - Francisco, Mart Ckerween (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the effects of artificial intelligence (AI) on the academic performance of Grade 8 students in selected public secondary schools under the Jalajala Sub-Office, Division of Rizal, including Jalajala National High School, Bayugo National High School, and Bagumbong National High School. Employing a descriptive survey research design, the study involved 306 respondents, representing half of the total Grade 8 student population. Data were gathered using a researcher-made questionnaire assessing the extent of AI’s effects in terms of motivational drive, concept and skills acquisition, and task completion. Documentary analysis of students’ first-quarter grades was also conducted to measure academic performance.Findings revealed that the majority of respondents were 13-year-old female first-borns from families with three to five children and with a monthly income of ₱10,000 and below. Parents were generally high school graduates, with fathers employed and mothers often unemployed. Students reported moderate use of AI tools and perceived their effects on motivation, skills acquisition, and task completion to a high extent. Academic performance was generally satisfactory, with most students obtaining grades within the 80–84 range. Statistical analysis showed no significant difference in the perceived effects of AI when respondents were grouped according to profile variables. Furthermore, no significant relationship was found between the extent of AI’s effects and students’ academic performance. These results suggest that while AI enhances engagement and learning processes, it does not directly influence academic achievement.The study concludes that AI can support learning experiences but should be complemented with other academic interventions. It is recommended that schools implement structured AI integration programs, provide training for effective use, ensure equitable access, and engage parents in supporting AI-assisted learning. Future studies may explore mediating factors that strengthen the relationship between AI use and academic outcomes..
Keywords: artificial intelligence, academic performance, Grade 8 students, motivation, skills acquisition, task completion, descriptive survey, secondary education